Pelaksanaan Rekruitmen dan Seleksi Dosen Keperawatan - Maria Agustina Ermi Tri Sulistiyowati Sulistiyowati (Jurnal Keperawatan Notokusumo, 2018)
Background: Lecturer as one of human resource in higher education has function, role, and position very strategic in realizing development of education field. The mistake in choosing the right lecturer is very big impact for the college. This study aims to determine the implementation of recruitment and selection of lecturers. Method: The research type is qualitative research with phenomenology study approach. The main informants were taken with purposive sampling technique. Data collection was done with in-depth interviews and observation. Results: The study resulted in one theme, which is not optimal faculty recruitment and selection processes. This theme is composed of three sub themes, which are not optimal recruitment planning and selection of lecturers, not adhered to lecturer qualification standards, and the absence of recruitment and lecturer selection team. Conclusion: The study resulted in one theme, which is not optimal faculty recruitment and selection processes. Suggestions: Leader universities need to rethink the policy of faculty recruitment and selection processes and improving the role of personnel to improve the implementation of recruitment and selection of lecturers